Evidence of Microbursts Observed Near the Equatorial Plane in the Outer Van Allen Radiation Belt. Issue 16 (27th August 2018) - Shumko, Mykhaylo; Turner, Drew L.; O'Brien, T. P.; Claudepierre, Seth G.; Sample, John; Hartley, D. P.; Fennel, Joseph; Blake, J. Bernard; Gkioulidou, Matina; Mitchell, Donald G.
Abstract: We present the first evidence of electron microbursts observed near the equatorial plane in Earth's outer radiation belt. We observed the microbursts on 31 March 2017 with the Magnetic Electron Ion Spectrometer and Radiation Belt Storm Probes Ion Composition Experiment on the Van Allen Probes. Microburst electrons with kinetic energies of 29–92 keV were scattered over a substantial range of pitch angles, and over time intervals of 150–500 ms. Furthermore, the microbursts arrived without dispersion in energy, indicating that they were recently scattered near the spacecraft. We have applied the relativistic theory of wave‐particle resonant diffusion to the calculated phase space density, revealing that the observed transport of microburst electrons is not consistent with the hypothesized quasi‐linear approximation. Plain Language Summary: Microbursts are a subsecond impulsive increase of electron precipitation from the outer Van Allen radiation belt into the atmosphere, believed to be an important loss process of radiation belt electrons. One possible source of microbursts is scattering of trapped radiation belt electrons by a plasma wave called chorus. Diffusion models show that chorus can both accelerate and scatter electrons into the atmosphere. Since microbursts have been previously observed by high‐altitude balloons and low Earth orbiting spacecraft, there has been little evidence that directly link the chorus wave and the microburst that it generated. We show evidence of microbursts and their progenitor waves observed deep inside the outer radiation belt by the Van Allen Probes spacecraft. The Van Allen Probes are configured to extensively study the wave and particle environment in the magnetosphere, which allows us to understand the microbursts' energy dependence, angular extent, and the scattering mechanism. This unique perspective enables us to understand how these electrons were transported by the chorus wave, and compare it to a hypothesized quasi‐linear diffusion model. Our results indicate that the observed transport of microburst electrons was not consistent with the hypothesized diffusion model. Key Points: The first report of direct observation of microbursts at high altitude, near the equatorial plane Microbursts' duration, flux enhancement, and energy spectra are similar to prior observations in LEO Microburst generation is not consistent with a single quasi‐linear gyroresonant interaction with chorus waves